"White graphene" – hexagonal boron nitride based polymeric composites and their application in thermal management. (November 2016) - Fang, Haoming; Bai, Shu-Lin; Wong, Ching Ping
Abstract: Thermal management is more and more crucial in advanced electronic devices with increasing power density. So, the demand for the materials with high thermal conductivity is rising. Hexagonal boron nitride (h-BN), called as "white graphene", has high thermal conductivity of 2000 W m −1 K −1 (by theoretical calculation) and is an electrical insulator, so h-BN filled polymer composite becomes a good candidate for potential employment in heat management of microelectronic devices. This paper gives a brief review on the development of h-BN based polymeric composites, including thermal transfer mechanism, fundamental design principle and application, as well as perspectives. Highlights: This paper gives a review of h-BN based polymeric composites in heat management. A facile method to get boron nitride nanosheets with large quantity is a challenge. High aspect ratio and orientation is a strategy to enhance thermal conductivity. 3D networks and hybrid fillers mixing are significant to form the heat pathway. Surface modification is a reasonable way to decrease the thermal resistance.